Impact of sodium glucose cotransporter 2 inhibitor on histological features and glucose metabolism of non‐alcoholic fatty liver disease complicated by diabetes mellitus - Akuta, Norio; Kawamura, Yusuke; Watanabe, Chizuru; Nishimura, Akihiro; Okubo, Minoru; Mori, Yasumichi; Fujiyama, Shunichiro; Sezaki, Hitomi; Hosaka, Tetsuya; Kobayashi, Masahiro; Kobayashi, Mariko; Saitoh, Satoshi; et al. (Hepatology research, 2019)
Aim The aim of this study was to investigate the therapeutic potential of sodium glucose cotransporter 2 inhibitor (SGLT2I) as an effective therapeutic option for non‐alcoholic fatty liver disease (NAFLD). Methods In this prospective study, nine patients with NAFLD complicated by type 2 diabetes mellitus (DM), were introduced to the regimen of canagliflozin 100 mg once daily for 24 weeks and were evaluated by liver histology at pretreatment and at 24 weeks after the start of treatment. The primary outcome was histological improvement, defined as a decrease in NAFLD activity score of one point or more without worsening in fibrosis stage. Glucose metabolism was evaluated based on the meal tolerance test. The usefulness of extracellular and exosome microRNA‐122 (miR‐122) as early predictors of histological improvement was investigated. Results All of the nine patients achieved histological improvement. Scores of steatosis, lobular inflammation, ballooning, and fibrosis stage decreased by 78%, 33%, 22%, and 33% at 24 weeks compared to the pretreatment, respectively. Six patients showed improvement in insulin resistance, and the other three patients showed partial improvement of insulin secretion function. Six patients, who showed a decrease in both extracellular and exosome miR‐122 ratios (the ratio of miR‐122 levels at 1 day after treatment to that at baseline), showed histological improvement. Furthermore, one patient, who showed a decrease in exosome miR‐122 ratios regardless of the increase in extracellular miR‐122 ratios, also showed decreases in NAFLD activity score and fibrosis stage. Conclusion A prospective study showed that SGLT2I for NAFLD complicated by DM improved histological features in connection with glucose metabolism. This trial was registered as clinical trial UMIN000018166.